The chromatic index of cyclic Steiner 2-designs - Charles J. Colbourn; Marlene J. Colbourn (International Journal of Mathematics and Mathematical Sciences)
The number of colours needed to colour the blocks of a cyclic Steiner 2-design S(2,k,v) is at most v.